Immune Response Regulation by Antigen Receptors’ Clone-Specific Nonself Parts - Lemke, Hilmar (Frontiers in Immunology, 2018)
Antigen determinants (epitopes) are recognized by the combining sites (paratopes) of B and T cell antigen-receptors (BCR/TCR), which again express clone-specific epitopes (idiotopes) that can be recognized by BCR/TCR not only of genetically different donors but also within the autologous immune system. While xenogeneic and allogeneic anti-idiotypic BCR/TCR are broadly cross-reactive, only autologous anti-idiotypes are truly specific and of functional regulatory relevance within a particular immune system. Autologous BCR/TCR idiotopes are (a) somatically created at the third complementarity-determining regions (CDR3), (b) through mutations introduced into BCRs during adaptive immune responses and (c) through the conformational impact of both. As these idiotypic characters have no genomic counterparts they have to be regarded as antigen receptor-intrinsic nonself-portions. Although foreign, however, they are per se non-immunogenic, but in conjunction with immunogenicity- and adjuvanticity-providing antigen-induced immune responses they induce abating regulatory idiotypic chain reactions. The dualistic nature of antigen-receptors of seeing antigens (self and nonself alike) and being nonself at the same time has far reaching consequences for an understanding of the regulation of adaptive immune responses.